NEEDS ASSESSMENT OF LEADERSHIP TRAINING & DEVELOPMENT PROGRAM: A CASE STUDY AT INDONESIA’S NATIONAL AGENCY OF POPULATION AND FAMILY PLANNING (BKKBN) - Masrinto Pongrambu; Patreeya Kitcharoen (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Leadership training and development (pendidikan dan pelatihan kepemimpinan or diklat kepemimpinan, mostly known its shorten Diklatpim) has become one of the most important training for Indonesia’s Civil Servants (Pegawai Negeri Sipil, or PNS), not excluded civil servants of Indonesia’s National Population and Family Planning Agency (Badan Kependudukan dan Keluarga Berencana Nasional, abbreviated BKKBN). This study aims to investigate the current and expected situation or condition of leadership training of BKKBN. Methods: This is a need assessment study that used mix methods to collect data from respondents. However, this issue shows the quantitative data only. The data samples were collected from 146 alumni of Diklatpim (230 alumni from year 20015-2018). The data were analysed by descriptive statistics and Priority Needs Index (PNI). Results: In BKKBN leadership and development training, Self-mastery has current mean score 4.09; expected mean score 4.56; PNI modified score 0.114. Diagnostic-reading has current mean score 3.97; expected mean score 4.51; PNI modified score 0.136. Innovation has current mean score 3.82; expected mean score 4.37; PNI modified score 0.144. Effective-team has current mean score 4.11; expected mean score 4.60; PNI modified score 0.119. Change-project has current mean score 4.21; expected mean score 4.59; PNI modified score 0.092. Conclusions: Innovation agenda has the lowest mean score, while the Change project has the highest mean score. Consequently, Innovation agenda has the highest rank in term of Priority Needs Index (PNI), while the Change project has the lowest rank. However, the ranks have no meaning that Change project is less important to be improved in the future.